Una musa “Dal nome amabile” (STES. FR. 327, 1 FINGLASS)? - Recchia, Marco (Exemplaria Classica, 2021)
Stes. fr. 327 F. provides an invocation to the Muse to sing the love story of a boy and a girl. The last section of l. 1 is barely corrupted. Moving from a previous Meineke’s suggestion, I discuss the hypothesis that the Muse invocated could be Erato and that the corrupt words could contain an adjective originally referred to the Muse: if it is so, a possible correction could be ??????????. The reference to Erato as Muse “with a lovely name” could be supported by A. R. 3.5; Ov. Ars 2.16; Fast. 4.195-6.